The governance of sustainable development: the possible paradigm of the ILO - Cascante, Kattya; Quintero Lima, Mª Gema (Revista Española de Desarrollo y Cooperación, 2020)
The idea of sustainability has found a privileged continent in the 2030 Agenda, in which it manifests itself in three dimensions as a mandate for a human transformation. Its potential, however, seems hampered by the current limitations of global world governance. Beyond an anecdote, the International Labour Organization offers a possible paradigm of postmodern governance of sustainable development in the social dimension, based on the postulate of social justice and decent work. Model that could be extrapolated.
Keywords: 2030 Agenda; Governance; Sustainable development; International Labour Organization (ILO)